African Indigenous Research to Decolonisation of African Universities’ Curricula - Mogomme Masoga (African Journal of Political Science)
The phrase African indigenous research (AIR) depicts a novel research thrust that seeks a global entrance into the mainstream research assortment as a competitive area of study. A discourse on decolonisation attempts to reverse the gains of colonialism. Existing studies show that most (South) African universities’ curricula can be traced to the colonial era. A rereading of available scholarly conversations depicts some reluctance on the part of education authorities towards decolonising the (South) African universities’ curricula. It is in the context of the above that the present study engages conversations on decolonisation in order to establish a common ground that affords AIR a notable articulation on decolonisation of (South) African Universities’ curricula. The present research is anchored on a critical race theory (CRT) in which narrative inquiry as a methodological approach is utilised. Although the phrase African universities’ curricula is employed, the study will focus on the (South) African universities’ curricula as representative examples. The (South) African scenario is preferred as a case study due to the author’s familiarisation with (South) African universities as well as African decolonisation discourses. The study attempts to answer the following three questions (1) what motivated research conversations on decolonisation? (2) why is the study on decolonisation of the curricula in (South) African universities necessary? and (3) what is the global impact of decolonisation processes in (South) Africa?